Could tympanometric volume be a useful tool to predict the success of type I tympanoplasty in simple chronic otitis media - Ribeiro, Carla A.; Azevedo, Cátia C.; Miranda, Daniel A.; Mar, Fernando M.; Pereira, Sara M.; Vilarinho, Sérgio S.; Dias, Luís A. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: Middle ear aeration level is an important precursor of chronic otitis media (COM) and one predictive factor for tympanoplasty success. Tympanometry measures the volume of the external ear canal, middle ear cavity, aditus, and mastoid air cells in patients with tympanic membrane (TM) perforation. The aim of the study was to determine whether the pre-operative tympanometric volume and the interaural tympanometric volume differences in unilateral simple COM can predict the success of type I tympanoplasty. Methods: Retrospective analysis of type I tympanoplasties performed in adults between January 2017 and December 2020 in a tertiary hospital. Bilateral COM, revision surgery and tympanoplasty using cartilage grafts or associated with other procedures were excluded. Success was defined as no evidence of TM perforation on otoscopic examination and tympanogram, at least six months after surgery. Results: Sixty-one patients were evaluated. The mean age was 43 years old, and there was a female predominance (55.7%). The overall success rate was 77%. Location or size of perforation weren’t different among patients with and without surgical success. We found a statistically significant result (p=0.009) regarding interaural tympanometric volume differences, with a median of 2.7 ml (IQR 3.6) in the surgical success group and a median of 1.3 ml (IQR 1.26) in the recurrence group. 90.6% of patients with interaural tympanometric volume difference greater than 2 ml had successful surgery. Conclusions: A good aeration of middle ear, demonstrated by higher interaural tympanometric volume differences, can predict success of type I tympanoplasty.